Efficient access to 2-pyrones via carbene-catalyzed oxidative [3+3] reactions between enals and nitrogen ylides - Zheng, Pengcheng (2020)
Pyrones are important structural units in natural products and synthetic functional molecules. Here, we report a carbene-catalyzed oxidative [3+3] cycloaddition reaction between enals and nitrogen ylides for quick access to 2-pyrones. Inexpensive and easily prepared 2′-pyridinium acetophenone bromide salts are used as precursors of pyridinium ylides to react with enals in our catalytic reactions.